Multi‐population seedling and soil transplants show possible responses of a common tropical montane tree species (Weinmannia bangii) to climate change. (29th June 2020) - Tito, Richard; Vasconcelos, Heraldo L.; Feeley, Kenneth J.
Abstract: A possible response of many plant species to global warming is migration to higher elevations. However, these migrations may not be required if species can tolerate higher temperatures, or may be prevented if there are other factors such as changes in soil conditions that make upslope areas unsuitable. We used a set of 3‐year field transplant experiments in the remote Peruvian Andes to simulate two possible responses of an abundant tropical montane cloudforest tree species ( Weinmania bangii ) to global warming: (a) 'upward migration', in which case seedlings of W. bangii's were grown at their current elevation/temperature but in soils transplanted from higher elevations and (b) 'migration failure', in which case seedlings were transplanted downslope along with their home soils into areas that are 1°C or 2°C warmer. We conducted separate experiments with populations from the upper/leading edge, middle and lower/trailing edges of W. bangii's elevational/thermal range to assess the influence of local adaptation on responses to changes in temperature or soil. We found that seedling survival and growth were not affected by changes in soil conditions, regardless of the origin population. However, seedling survival decreased with temperature. A simulated warming of 1°C caused a significant reduction in the survival of seedlings transplanted from the mid‐range population, and 2°C warming caused a severe decrease in the survival of seedlings transplanted from both the mid‐range and bottom‐edge populations. Synthesis . Our findings reveal that rising temperatures are a serious threat to plants, especially in populations growing in the hotter portion of their species' range. At least in the case of W. bangii, novel soil conditions will not limit the establishment or growth of seedlings at higher elevations. As such, decreases in the survivorship at lower elevations may be offset through upward migrations as temperatures continue to increase. Abstract : Our findings reveal that rising temperatures are a serious threat to plants, especially in populations growing in the hotter portion of their species' range. At least in the case of W. bangii, novel soil conditions will not limit the establishment or growth of seedlings at higher elevations. As such, decreases in the survivorship at lower elevations may be offset through upward migrations as temperatures continue to increase. Resumen: Una posible respuesta de muchas especies de plantas al calentamiento global es la migración a mayores elevaciones. Sin embargo, estas migraciones pueden no ser necesarias si las especies toleran temperaturas más altas, o la migración puede ser limitada por otros factores como los cambios en las condiciones del suelo, haciendo que a mayores elevaciones sean áreas inadecuadas. Utilizamos un conjunto de experimentos de trasplante en campo (durante tres años) en áreas remotas en los Andes del Perú para simular dos posibles respuestas de una especie de árbol abundante del bosque nublado andino ( Weinmania bangii ) al calentamiento climático: (a) "migración ascendente", en el que las plántulas de W. bangii se trasplantaron en la misma elevación/temperatura actual pero con suelo traído desde elevaciones más altas; y (b) "falla en la migración", en cuyo caso las plántulas juntamente con suelos de la misma elevación se trasplantaron cuesta abajo, a elevaciones que presentan 1°C ó 2°C más cálidas. Para evaluar la influencia de la adaptación local en las respuestas a los cambios en la temperatura o suelo, realizamos experimentos separados para poblaciones del borde superior, medio y borde inferior del rango altitudinal/térmico de W. bangii . Encontramos que la sobrevivencia y crecimiento de las plántulas no fueron afectados por los cambios en las condiciones del suelo, independientemente de la población origen. Sin embargo, la sobrevivencia de las plántulas disminuyó con la temperatura. Un calentamiento simulado de 1°C causó una reducción significativa en la sobrevivencia de las plántulas trasplantadas de la población del rango medio, y el calentamiento de 2°C causó una disminución severa en la sobrevivencia de las plántulas trasplantadas de las poblaciones de rango medio e inferior. Síntesis . Nuestros resultados revelan que el aumento de la temperatura es una amenaza real para las plantas, especialmente en las poblaciones que crecen en la parte más cálida del rango de distribución de la especie. Al menos en caso de W. bangii, las nuevas condiciones del suelo no limitarán el establecimiento o el crecimiento de plántulas a elevaciones más altas. Así, las disminuciones en la sobrevivencia en elevaciones más bajas podría ser compensada por las migraciones ascendentes a medida que la temperatura continúe aumentando.